Translating English Modal Auxiliary Verbs into Indonesian: A Case Study of Broken Strings - Lola Deliva; Wahyu Budi (Jurnal Pendidikan dan Sastra Inggris, 2026)
Translating English modal auxiliary verbs into Indonesian presents a unique linguistic challenge because the two languages express modality through entirely different grammatical structures. In literary texts, these verbs do far more than indicate tense or possibility; they are crucial for establishing tone, perspective, and character depth. Despite their narrative weight, modal verbs are often overlooked in English-Indonesian literary translation studies. This study addresses the gap by identifying the core modal auxiliary verbs in Aurélie Moeremans’s memoir Broken Strings and analyzing how they are rendered into Indonesian. Utilizing a descriptive qualitative approach supported by quantitative data, the study tracked nine core modals—can, could, may, might, must, shall, should, will, and would—through the lens of Molina and Albir’s (2002) translation techniques framework. The analysis revealed 682 total occurrences, with could appearing most frequently at 245 instances (35.92%), followed by would at 216 instances (31.67%). Five specific translation techniques emerged: established equivalent, reduction, transposition, modulation, and variation. Established equivalent was the dominant strategy, used in 382 cases (56.01%), which underscores the translator’s strong preference for natural Indonesian phrasing over the rigid preservation of English grammatical forms. Ultimately, the study demonstrates that translating modal verbs relies heavily on contextual nuance and communicative intent, requiring flexible structural and semantic shifts to ensure clarity and readability in the target text.